898 The Fragility Fracture Post-Operative Mobilisation (FFPOM) Study – a UK-Wide Audit of Lower-Limb Fragility Fractures. (19th August 2022) - Zargaran, Alexander; Bretherton, Christopher; Richardson, Charlotte; Raza, Mohsen; Eardley, William; Trompeter, Alex
Abstract: Aim: This study quantifies the epidemiology and weight-bearing practice of operatively managed fragility fractures of the lower limb in the National Health Service. Method: A multicentre audit of all adult patients aged 60 and over receiving surgery for a fragility fracture of the lower limb between 01/01/2019–30/06/2019 and 01/02/2021–14/03/2021 was conducted. The British Orthopaedic Association (BOA) guidance was used as the standard. Results: 430 collaborators from 84 hospitals submitted data from 20193 patients. 19557 patients with a median age of 83 (70.4% female) were included in the analysis. Data from 16241 hip fracture patients and 3316 non-hip fracture patients were analysed. In the non-hip fracture population, the most common fractures were of the foot and ankle (45.1%). 15543 (95.7%) of hip fracture and 1071 (32.3%) non-hip fracture patients were allowed to weight-bear immediately post-operatively. Despite being demographically similar, the proportion of patients instructed to weight-bear without restriction following operative fixation of the shaft (47.8%) and distal (64.6%) femur was lower than patients receiving surgery for a proximal femoral fracture (95.7%). 45.6% of distal femur and 44.2% of femoral shaft fractures were periprosthetic compared to 2.2% of proximal femur fractures. Conclusions: This UK-wide collaborative study of over 19, 000 patients demonstrates a significant disparity in weight-bearing restrictions placed on patients with fragility fractures despite the publication of a national guideline. Surgeons intentionally restrict post-operative weight-bearing in the majority of fractures outside the hip, but by contrast are content with unrestricted weight-bearing following operations for hip fracture.